S-Calprotectin (S100A8/S100A9): A Potential Marker of Inflammation in Patients with Psoriatic Arthritis. (14th May 2014) - Hansson, Claes; Eriksson, Catharina; Alenius, Gerd-Marie
Abstract : Objective . To analyse levels of S100A8/S100A9 (calprotectin) and selected cytokines, in blood, in patients with psoriatic arthritis (PsA). Methods . Sixty-five patients with PsA were examined for clinical manifestations and laboratory measurements of S-calprotectin, ESR, hs-CRP, and selected cytokines. Thirty-two patients had mono-/oligoarthritis and 33 had polyarthritis. S-calprotectin, hs-CRP, and cytokines were measured using ELISA, immunoturbidimetry, and multiplex technology (Bio-Plex). Patients with PsA were compared with 31 healthy controls. Results . S-calprotectin and hs-CRP levels were significantly higher in patients with PsA compared with controls (P < 0.001 and P < 0.001, resp.). Patients suffering a polyarthritic disease pattern presented with significantly higher levels of S-calprotectin compared with controls and patients with mono-/oligoarthritis (P < 0.001 and P = 0.017, resp.). The levels of S-calprotectin correlated with hs-CRP (P < 0.001 ; r s = 0.441 ), swollen joint count (P = 0.002, r s = 0.397 ), and CXCL10 (P = 0.046, r s = 0.678 ) but not with any of the other cytokines evaluated. In multiple logistic regression analysis, S-calprotectin was the only variable significantly associated with psoriatic arthritis (P = 0.002, OR = 1.006, 95% CI = 1.002–1.010). Conclusion . S-calprotectin and hs-CRP levels were significantly higher in patients with PsA. A polyarthritic disease pattern showed higher levels of S-calprotectin than mono-/oligoarthritis. S-calprotectin is considered a potential marker of disease activity in patients with PsA.